Formation of National and International Associations of Medical and Health Sciences Libraries - Güneş, Güssün (Information World, 2007)
Medical libraries play important roles in classifying, storing and providing access to medical information. Medical libraries are in steady development ever since 1850’s. This study reviews the formation of associations among modern medical libraries, and also refers to the medical and health science library associations in Turkey. In that connection, a mention was also made to the work of the ÜNAK Medical and Health Sciences Working Group.